Challenges in the preclinical design and assessment of CAR-T cells - Tomai, Radu; De Las Rivas, Javier; Fetica, Bogdan; Bergantim, Rui; Filipic, Brankica; Gagic, Zarko; Nikolic, Katarina; Gulei, Diana; Kegyes, David; Nistor, Madalina; Muresan, Ximena Maria; Cenariu, Diana; et al. (Frontiers in Immunology, 2025)
The advent of immunotherapy in the treatment of cancer has opened a new dimension in the management of this complex multifaceted disease, bringing hope to many patients whose tumors have failed to respond to conventional therapies. The adoptive T cell therapy has since been extended to the treatment of several hematologic malignancies, initially in relapsed settings and more recently at the forefront of treatment due to high response rates. Despite exciting initial results, the preclinical antitumor effects of the first long-term studies show that CAR (Chimeric Antigen Receptor)-T cells have been slow to translate to the clinical setting, with early clinical trials showing suboptimal responses. The main reasons for the limited clinical performance seemed to be related to the low activation and short persistence of CAR-T cells. Thus, began a journey to improve the initial CAR structure, leading to the development of more complex constructs, which are grouped into five CAR generations. In this review, we describe the main challenges and potential solutions for the evaluation of CAR T-cell-based therapies in the preclinical setting.